Determinan Minat Beli Makanan dan Minuman pada Restoran Korea di Jabodetabek - rahmi, Mira; Tsaniya Al-Labiyah, andira (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Abstract South Korean culture has a considerable influence in several countries, one of which is Indonesia. The great interest of the public in Korean culture has given rise to buying interest in consuming everything related to South Korea as a lifestyle followed by young people, in particular, one of which is for South Korean specialties. This situation can be an opportunity for entrepreneurs to serve food products with a South Korean-style taste and atmosphere that is implemented with Korean restaurant businesses or businesses, but the consumption of South Korean-style food has not been accompanied by awareness of halal products. The purpose of this study is to find out how consumers' tendency to buy food from Korean restaurants in Greater Jakarta is influenced by factors such as lifestyle, price, and halal awareness. This study utilizes a quantitative approach through the application of the multiple linear regression method. The population of this study is the Muslim population who know halal Korean restaurants in Greater Jakarta. The results of this study prove that lifestyle, price, and halal awareness have an influence on buying interest in Korea Jabodetabek restaurants. The halal Korean restaurant industry in Greater Jakarta should consider lifestyle trends, maintain service quality with prices and halal foodstuffs.. Keywords: lifestyle, prices, halal awareness, Korean restaurant. Abstrak Budaya Korea Selatan mempunyai pengaruh yang cukup besar di beberapa negara, salah satunya di Indonesia. Besarnya ketertarikan masyarakat kepada budaya Korea memunculkan minat beli dalam mengkonsumsi segala sesuatu yang berkaitan dengan Korea Selatan sebagai gaya hidup yang diikuti oleh kalangan anak muda khususnya, salah satunya terhadap makanan khas Korea Selatan. Situasi ini dapat menjadi kesempatan bagi pengusaha untuk menyajikan produk makanan dengan cita rasa dan atmosfer ala Korea Selatan yang diimplementasikan dengan usaha atau bisnis restoran Korea, namun konsumsi makanan ala korea selatan ini belum barengi dengan kesadaran akan kehalalan produk. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana kecenderungan konsumen untuk membeli makanan dari restoran Korea di jabodetabek yang dipengaruhi oleh faktor-faktor seperti gaya hidup, harga, dan kesadaran halal. Studi ini memanfaatkan pendekatan kuantitatif melalui penerapan metode regresi linier berganda. Populasi dari penelitian ini yaitu penduduk muslim yang mengetahui restoran Korea halal di jabodetabek. Hasil dari penelitian ini membuktikan bahwa gaya hidup, harga, dan kesadaran halal memiliki pengaruh terhadap minat beli di restoran Korea jabodetabek. Industri restoran Korea halal di jabodetabek agar mempertimbangkan trend gaya hidup, menjaga kualitas pelayanan dengan harga serta kehalalan pada bahan makanan. Kata kunci: gaya hidup, harga, kesadaran halal, restoran Korea.